APPLICATION OF PROJECT-BASED LEARNING METHOD TO IMPROVE 21ST CENTURY SKILLS - Novi Sriwulandari; Peni Astuti; Munawir Anas (Adisam Publisher, 2025)
The purpose of this project is to investigate in detail how the Project-Based Learning (PjBL) approach is used to help students develop 21st-century abilities. 21st-century abilities, such as communication, teamwork, creativity, and critical thinking, are essential in facing global challenges in the digital era. Using a literature review approach, this study collects and analyzes various previous study results that are relevant to the implementation of PjBL at various levels of education. The results of the study indicate that the PjBL method consistently makes a positive contribution to the development of 21st-century skills. PjBL encourages students to be actively involved in the learning process through real-world problem solving and collaborative group work. In addition, the integration between the learning process and the use of technology in PjBL further strengthens the achievement of skills needed in the modern era. This study concludes that PjBL is one of the effective and relevant pedagogical approaches in supporting competency-based learning in the 21st century. Competent teacher support and a conducive learning environment are needed to optimize the implementation of this method sustainably.